ARCHEOLOGICZNE Ścieżki SEWERYNA TYMIENIECKIEGO – KWIATKÓW W BADANIACH ARCHIWALNYCH KALISKIEGO PRAWNIKA - Kot -Legieć, Karolina (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2020)
This article is meant to present and verify historical objects discovered in Kwiatków (Gaj) village by Seweryn Tymieniecki (1847-1916). These relics (related to the Lusatian and Przeworsk cultures) are a good pretext for presenting the lawyer from Kalisz who was also an avid fan of archaeology. On top of a collection of interesting artefacts, Tymieniecki described equally intriguing burial forms. He made a name for himself in literature on the subject owing to his activity in the field followed by numerous publications in which he presented the effects of his surveys in a professional and competent way. It took 130 years before Tymieniecki’s name appeared again in archaeological literature. However, this time it was an entirely different quality of research, with respect to the methodology as well as the results of the work.